GAYA KOMUNIKASI CALON ANGGOTA LEGISLATIF MUDA TERHADAP PEMILIH GENERASI Z DI PEMILU - Endayani, Endayani; Fitrianti, Rizqi; Fajarwati, Noerma Kurnia; Susilawati, Eka (Universitas Bina Bangsa, 2024)
The 2024 election in Indonesia faces the challenge of attracting the attention of Generation Z, young voters with unique characteristics and communication preferences. Legislative candidates are required to adjust their political communication styles to effectively capture interest and gain support from this generation. This study aims to analyze the political communication style employed by young legislative candidates in approaching Generation Z voters. The research method uses content analysis with a qualitative approach, examining communication styles through published content. The subjects of this study are young legislative candidates in the electoral district (Dapil) of Banten 1. The study concludes that to gain the attention and electability of Generation Z in the 2024 election, candidates should use an interpersonal communication style that is transparent and effective, utilizing visual aids and social media as primary platforms. Political communication that is simpler, relevant, effective, and authentic is the form of communication that Generation Z needs in the election